University-industry knowledge interaction in Switzerland: What university scientists think about co-operation with private enterprises - Spyros Arvanitis; Ursina Kubli; Martin Woerter (ETH Zurich, KOF Swiss Economic Institute, 2006)
This study explores the factors determining the propensity of Swiss science institutions at the level of a single institute or department to interact with private enterprises in Switzerland (universities and other research institution), i.e. to get involved in knowledge and technology transfer (KTT) activities in order to provide firms with scientific knowledge in research fields which are relevant for their own innovation activities, collect practical experience for students and university staff as well as test the applicability of new research results. We are especially interested in the different forms of this interaction, not only through joint research projects but also through training, mobility of academic personnel, jointly supervised master theses and PhDs, consulting and so on. Moreover, we also study the determinants of commercialization of university research output that takes the form of patenting, licensing or spin-offs. The data used in this study were collected in the course of a survey among institutes of all three types of science institutions in Switzerland (federal institutions, cantonalal universities and regional universities of applied sciences) using a questionnaire.
Keywords: O30; 330; knowledge and technology transfer; Forschungskooperation; Technologietransfer; Hochschulforschung; Schweiz; Meinung